IMPLEMENTATION OF FLIPPED CLASSROOM TO INCREASE STUDENT ACTIVITY, MOTIVATION, AND LEARNING OUTCOMES IN THE INTEGRATED GOVERNMENT GRADUATE PROGRAM (S1 PIN) MULAWARMAN UNIVERSITY - Zaenab Hanim; Rabiyatun Ummu Kaltsum A; Rahmat Soe’oed (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
Lectures become the center of learning who dominate the activities in traditional classrooms. Most of the learning time in the classroom is spent on lecturing than students' activities which causes a lack of motivation in learning. The study aims to: 1) increase activities of both the lecture and students by implementing Flipped Classroom; 2) to increase students' motivation by implementing Flipped Classroom; 3) to increase students' learning achievement by implementing Flipped Classroom. The study used a classroom action research methodology which consisted of 3 cycles. There were four stages in the research: planning, implementation, observation, and reflection. Data of the study consisted of 1) activities data of both lecture and students through observation and documentation; 2) students' motivation data through online questionnaires on Google Form and observation; 3) learning achievement through an online quiz on Edmodo. At the end of Cycle III, it was found out that there was an increase in activities of both lecture and students, student motivation, and learning achievement by implementing Flipped Classroom.